Ilhas de Croatã – A territorialidade de ações artísticas e espaços públicos (Palíndromo, 2014)
Influenced by the counterculture movement Provos (1965), the poetic narrative Islands of Croatan presents a brief analysis of its two artistic actions: in the experimental implementation of a white bicycle as collective, public and free transportation, inserted in the campus of UNESP/Bauru; and in TRANSITOSensorium action, deterritorializing an imaginary city from QRcodes throughout the city of Bauru, where the user finds a hybridity between visual, sound and written languages. The research relates the idea of territory through a relationship between space and power, listing the concepts of Psychogeography - the study of affective actions in collective space and Tempo- rary Autonomous Zones. This is an experimental study, with the insertion of new technologies.
Keywords: terretory; actions; appropriation; deterritoriallization and art